Age and sex‐specific mortality of wild and captive populations of a monogamous pair‐bonded primate (Aotus azarae). Issue 3 (10th April 2015) - Larson, Sam M.; Colchero, Fernando; Jones, Owen R.; Williams, Lawrence; Fernandez‐Duque, Eduardo
Abstract : In polygynous primates, a greater reproductive variance in males have been linked to their reduced life expectancy relative to females. The mortality patterns of monogamous pair‐bonded primates, however, are less clear. We analyzed the sex differences in mortality within wild ( N Males = 70, N Females = 73) and captive ( N Males = 25, N Females = 29) populations of Azara's owl monkeys ( Aotus azarae ), a socially and genetically monogamous primate exhibiting biparental care. We used Bayesian Survival Trajectory Analysis (BaSTA) to test age‐dependent models of mortality. The wild and captive populations were best fit by the logistic and Gompertz models, respectively, implying greater heterogeneity in the wild environment likely due to harsher conditions. We found that age patterns of mortality were similar between the sexes in both populations. We calculated life expectancy and disparity, the latter a measure of the steepness of senescence, for both sexes in each population. Males and females had similar life expectancies in both populations; the wild population overall having a shorter life expectancy than the captive one. Furthermore, captive females had a reduced life disparity relative to captive males and to both sexes in the wild. We interpret this pattern in light of the hazards associated with reproduction. In captivity, where reproduction is intensely managed, the risks associated with gestation and birth are tempered so that there is a reduction in the likelihood of captive females dying prematurely, decreasing their overall life disparity. Am. J. Primatol. 78:315–325, 2016. © 2015 Wiley Periodicals, Inc.